Application Development 2013 Curriculum Report : Pengembangan Aplikasi Raport Kurikulum 2013 - Mochammad Hasyim Asy’Ari; Rahmania Sri Untari; Fitria Nur Hasanah (Universitas Muhammadiyah Sidoarjo, 2021)
In SMA Dian Indonesia the report card data entry process is still constrained by the complexity of the application flow that is used. Each subject teacher gives a grade to the homeroom teacher to be processed into a report card. This made it difficult for the homeroom teacher to process the data provided by the subject teacher so that the process of processing report cards was hampered.